P-475 Similar fertilization rates and preimplantation embryo development among testosterone-treated transgender men and cisgender women. (30th June 2022) - Israeli, T; Preisler, L; Kalma, Y; Samara, N; Levi, S; Groutz, A; Azem, F; Amir, H
Abstract: Study question: What are the effects of testosterone treatment on fertilization rates and preimplantation embryo development among transgender men who underwent fertility preservation? Summary answer: Testosterone exposure among transgender men has no adverse impacts on fertilization rates and preimplantation embryo development and quality. What is known already: Transmen are assigned female sex at birth but identify as men. This mismatch might induce distress that is termed gender dysphoria. Testosterone therapy induces "masculine" physical traits, suppresses "feminine" ones, and relieves gender dysphoria. More transmen present for testosterone therapy, their average age is decreasing, and many express the desire to have biological children. Therefore, understanding the effects of testosterone on fertility is crucial. Previous data suggest that despite testosterone treatment, the ovarian reserve and the in-vitro oocyte maturation are preserved among transmen. However, the fertility potential in terms of fertilization rate and early embryo development was not explored. Study design, size, duration: This retrospective cohort study included 7 testosterone-treated transgender men and 34 cisgender women between April 2016 and November 2021. Participants/materials, setting, methods: Testosterone-treated transgender men who cryopreserved embryos were compared to 10 fertile women who cryopreserved embryos and to 24 women who underwent IVF treatment due to unexplained or mechanical infertility. Statistical analyses compared assisted reproductive technology data and outcomes between the transgender men group and the two cisgender women groups. Morphokinetic and morphological parameters were compared between 210 embryos of transgender men and 411 embryos of cisgender women. Main results and the role of chance: The transgender men (30.2±3.59 years) were significantly younger than the cisgender women who cryopreserved embryos (35.1±1.85 years; P = 0.005) and the cisgender women who underwent fertility treatment (33.8±3.23 years; P = 0.017). Among the transgender men, the mean length of testosterone exposure was 99.7±49.24 months (range 14-156 months) and the mean time of discontinuation of testosterone prior to stimulation was 6.57±2.14 months (range 4-10 months). After adjusting for the patient's age, the fertilization rate was comparable between the transgender men and both cisgender women groups ( P = 0.391 and 0.659). No significant differences in the number of cryopreserved embryos (7.2±5.09 and 3.5±2.66; P = 0.473) and the days on which they were frozen ( P = 0.576) were observed between the transgender men and the fertile cisgender women. All morphokinetic parameters that were evaluated using time-lapse imaging, as well as the morphological characteristics, were comparable between transgender men and both groups of cisgender women. Limitations, reasons for caution: All transgender men in our study discontinued the testosterone treatment before starting ovarian stimulation. Stopping hormonal therapy might cause considerable anguish and gender dysphoria. Therefore, further studies that include subjects who did not stop testosterone before fertility preservation are needed. Wider implications of the findings: Transgender men have acceptable fertilization rates and normal preimplantation embryo development and quality after long-term testosterone treatment. Embryo cryopreservation is, therefore, a feasible and effective way for them to preserve their fertility for future biological parenting. Trial registration number: Not applicable